Determination of the electrical power increase at the generator terminals of a nuclear power plant unit at different condenser states - Bratkovska, Kateryna; Liush, Yuliya (Eastern-European Journal of Enterprise Technologies, 2021)
It is shown that the technical condition of condensing devices of steam turbines largely determines the amount of electricity losses, reliable and economical operation of NPP units. Analysis of the heat transfer process in the condenser showed that the main causes of load reduction are determined by rising cooling water temperature and deviation of steam pressure from normal value. It is shown that among diagnostic parameters except leakage volumes there must be an assessment of contamination of the heat transfer surface which significantly affects the reduction of electricity generation. The modernization main points of the condenser of the Zaporizhzhya NPP power unit No. 3 on the principle of "block-modular" design developed by PJSC "Turboatom" and the characteristics of the condenser provided by the new design are considered. To reflect the real mode of operation of the condensing unit, it is proposed to model the contamination of the heat exchange surface and the presence of leakages in the condenser space using the method of thermal calculation of the condenser by iterative methods. It was found that reducing the increase in electricity generation as a result of the effects of the study factors can partially or even completely absorb the effect of upgrading the condenser plant. It will provide a significant increase in electricity generation with relatively low capital investment compared to construction of new NPP power units and improve the accuracy of power generation forecasts.